Short-term effectiveness of a culturally tailored educational intervention on foot self-care among type 2 diabetes patients in Morocco - Latifa Adarmouch; Abdelhadi Elyacoubi; Latifeh Dahmash; Nawal El Ansari; Majda Sebbani; Mohamed Amine (Journal of Clinical & Translational Endocrinology, 2017)
Background: Self-management education (SME) is an important yet unacknowledged aspect of diabetes care. Despite the raise of diabetes and its complications with significant burden in developing countries, research on SME interventions in Morocco is lacking. Aims: To assess the effectiveness of a culturally tailored SME intervention on foot-care self-management practices among type 2 diabetes patients and to identify factors associated with practices variation. Methods: We designed a pre-post prospective quasi-experimental study and recruited patients with type 2 diabetes aged 30 years old or above. The intervention consisted of an interactive group discussion using different materials: a narrative video, a PowerPoint presentation and a printed guide. Foot-care practices were assessed prior to the session and one month later using 2 items from the Summary of Diabetes Self-Care Activities (SDSCA). Binary logistic regression was performed to identify factors associated with a favorable variation, defined as an increase in the mean frequency score of foot-care by a minimum of 1 day/week. Results: A total of 199 participants were recruited and 133 completed the second assessment. Mean age was 55.2 ± 11.2 years old. Women represented 67% and 72% of participants was illiterate. The foot-care score mean increased from 3.5 ± 2.9 days to 5.9 ± 1.8 days one month after the intervention (mean variation was 2.4 ± 3.1 days; p < 0.001). A favorable variation was found among 75 (37.7%) participants. In multivariate analysis, literacy was associated with higher likelihood of a favorable variation of foot-care practices (OR = 2.82; 95%CI: 1.09–7.31) while previous education about diabetic foot was associated with lower likelihood of a favorable variation (OR = 0.26; 95%CI: 0.08–0.78). Conclusions: There was a general improvement in foot-care practices after the intervention. Our findings suggest the role of literacy and previous patient education in shaping the observed variation. Culturally tailored interventions targeting other disease management domains are needed in our context.